일제강점기 감화사업의 성격과 영향에 관한 연구 - 박정란; Park¸ Jungran (청소년복지연구, 2021)
본 연구는 일제강점기 식민지 한국에 이식된 감화사업의 특징과 영향을 고찰하고자 수행되었다. 본 연구결과 일본의 감화구제사업은 소년보호란 미시적 복지에 국한되지 않은 포괄적이고 거시적 국가정책이었다는 것과 그 실시배경이 ‘제국’으로서의 지위획득을 위한 지방개편의 일환이었다는 것이다. 본 연구는 공립 감화원으로 대표되는 식민지 한국의 감화사업의 특징을 다음 4가지로 분석함으로써 이것이 식민지정책의 일환으로 실시되었음을 밝혔다. 첫째, 일제는 감화원을 모두 고도(孤島)에 설치함으로써 원생들을 사회로부터 철저히 격리하였다. 둘째, 감화원 원생은 ‘사냥(狩り)’감과 ‘청소(一掃)’해야 할 ‘숙청’대상이었고 전쟁수행을 위한 인적자원으로 보았다. 셋째, 원생의 불량성은 부모의 나쁜 교육 외에도 유전적인 것으로 ‘우생사회사업’에서는 이를 단종의 대상으로 보기도 하였다. 넷째, 감화사업은 충량한 양민양성이란 강력한 정신주의 아래 원생들의 정신개조를 위한 가혹한 처우가 이루어졌다. 본 연구는 또한 일제강점기 감화사업이 독립후 한국사회복지에 미친 영향으로 일제 소년보호정책의 답습과 방치, 독립후에도 계속된 일제검거와 사회재건의 인적자원화, 우범소년에 대한 낙인, 그리고 한국의 사회복지실천의 뿌리 깊은 온정주의를 제기하였다. The purpose of this study was to consider the characteristic and impact of Inspirational relief work implemented during the Japanese Colonial era. Results of this study showed that Japanese inspirational relief work was conducted as part of the comprehensively and macroscopically colonial policy beyond juvenile protection. Japanese inspirational relief work was a kind of reorganizing local area in order to acquire a status as a empire. This study identified that Japanese inspirational relief work which represented the public relief work were as part of the colonial policy. For verifying this, the characteristics of Japanese inspirational relief work were categorized into 4 things. First, all the reformatories were built in remote islands, which made juveniles in the reformatories be thoroughly isolated from the society. Second, the juveniles in the reformatories were viewed as subjects of ‘purge’ who should be ‘hunted’ and ‘cleaned’. Also, they were treated as reserve forces for war. Third, the juveniles’ defectiveness was regarded as a result of genetic inferiority as well as their parents’ bad education, which was thought of as a thing necessary to be discontinued in the eugenic social policy. Fourth, the juveniles in the reformatories were treated harshly under the slogan of the powerful spiritual modification. This study also examined the influences of the inspirational relief work after independence on Korean social welfare; imitate and neglect of the Japanese youth protection policy, the continued arrest and human resourceization for social reconstruction by the Korean government after independence, stigma of delinquent juvenile, and deep-rooted paternalism of social welfare practice in Korea.